1999
DOI: 10.1007/s004410051340
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cell contacts in the human cell line ECV304 exhibit both endothelial and epithelial characteristics

Abstract: Endothelial cells separate the intra- and extravascular space and regulate transport processes between these compartments. Since intercellular junctions are required for these specific cell functions, the cell-cell contacts in the permanent cell line ECV304 were systematically analyzed and compared with human umbilical vein endothelial cells (HUVECs) in primary culture and with the epithelial Madin Darby Canine Kidney (MDCK) cell line. Filter-grown ECV304 cells generate a distinct electrical resistance and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 22 publications
3
38
1
Order By: Relevance
“…EaHy.926, a hybridoma of primary HUVEC and a human airway epithelial cell line (20), has been previously shown to behave similarly to primary endothelial cells in vitro, expressing high levels of the endothelial specific marker, CD31, as well as retaining the ability to up-regulate HLA-DR and cause proliferation of allospecific T cells in vitro (16,21). In contrast, the second cell line we have transfected is a bladder epithelial carcinoma T24 (previously misidentified as a spontaneously transformed endothelial cell line ECV.304) (22). This cell line does not express HLA-class II determinants after IFN-␥ stimulation for several days, while responding with up-regulation of other molecules influenced by IFN-␥ treatment (21).…”
mentioning
confidence: 99%
“…EaHy.926, a hybridoma of primary HUVEC and a human airway epithelial cell line (20), has been previously shown to behave similarly to primary endothelial cells in vitro, expressing high levels of the endothelial specific marker, CD31, as well as retaining the ability to up-regulate HLA-DR and cause proliferation of allospecific T cells in vitro (16,21). In contrast, the second cell line we have transfected is a bladder epithelial carcinoma T24 (previously misidentified as a spontaneously transformed endothelial cell line ECV.304) (22). This cell line does not express HLA-class II determinants after IFN-␥ stimulation for several days, while responding with up-regulation of other molecules influenced by IFN-␥ treatment (21).…”
mentioning
confidence: 99%
“…One report, using a continuous ECV304 cell line, suggested that dengue virus interacted with 3 undefined cellular proteins (78). However, these interactions have not been studied further or analyzed in primary human endothelial cells (2,12,41,44).…”
mentioning
confidence: 99%
“…ECV304 cells maintain typical cobblestone morphology, form lateral membrane interdigitations that prevent the diffusion of lanthanum, and respond to classical and selective endothelial stimulants such as ionomycin, ADP, vascular endothelial growth factor, bradykinin, angiotensin, and oxidized low density lipoprotein (13)(14)(15)(16)(17)(18)(19)(20). The ECV304 cells express classical endothelial receptors such as thrombomodulin and vitronectin receptor CD51, and are capable of secreting plasminogen activator inhibitor-1 and endothelin (21). However, during transformation the cells lost the ability to generate nitric oxide and have acquired phenotypic expression of epithelial proteins such as E-cadherin and desmosomal proteins (21,22).…”
mentioning
confidence: 99%
“…The ECV304 cells express classical endothelial receptors such as thrombomodulin and vitronectin receptor CD51, and are capable of secreting plasminogen activator inhibitor-1 and endothelin (21). However, during transformation the cells lost the ability to generate nitric oxide and have acquired phenotypic expression of epithelial proteins such as E-cadherin and desmosomal proteins (21,22). Therefore, although these cells express all of the classical endothelial markers in culture, they have differentiated toward an epithelium-like phenotype (22).…”
mentioning
confidence: 99%